Ecologic observations on the fauna associated to the cystoseira belt along the romanian Black Sea coast - Țigănuș, Victoria (Cercetări Marine - Recherches Marines, 2026)
The data reported concern the composition, distribution and monthly variation of the invertebrate fauna associated to the alga Cystoseira barbata Ag. along the Romanian Black Sea coast. The study was carried out during summer season (May to November). The results were compared with the data in the literature referring to other areas of the Black Sea.